Dynamic Responses of Female Volunteers in Rear Impact Sled Tests at Two Head Restraint Distances - Carlsson, Anna; Horion, Stefan; Davidsson, Johan; Schick, Sylvia; Linder, Astrid; Hell, Wolfram; Svensson, Mats Y. (Frontiers in Bioengineering and Biotechnology, 2021)
The objective of this study was to assess the biomechanical and kinematic responses of female volunteers with two different head restraint (HR) configurations when exposed to a low-speed rear loading environment. A series of rear impact sled tests comprising eight belted, near 50th percentile female volunteers, seated on a simplified laboratory seat, was performed with a mean sled acceleration of 2.1g and a velocity change of 6.8 km/h. Each volunteer underwent two tests; the first test configuration, HR10, was performed at the initial HR distance 10 cm and the second test configuration, HR15, was performed at 15 cm. Time histories, peak values and their timing were derived from accelerometer data and video analysis, and response corridors were also generated. The results were separated into three different categories, HR10C (N=8), HR15C (N=6) and HR15NC (N=2), based on: 1) the targeted initial HR distance [10 cm or 15 cm] and 2) whether the volunteers’ head had made contact with the HR [Contact (C) or No Contact (NC)] during the test event. The results in the three categories deviated significantly. The greatest differences were found for the average peak head angular displacements, ranging from 10° to 64°. Furthermore, the average neck injury criteria (NIC) value was 22% lower in HR10C (3.9 m2/s2), and 49% greater in HR15NC (7.4 m2/s2) in comparison to HR15C (5.0 m2/s2). This study supplies new data suitable for validation of mechanical or mathematical models of a 50th percentile female. A model of a 50th percentile female remains to be developed and is urgently required to complement the average male models to enhance equality in safety assessments. Hence, it is important that future protection systems are developed and evaluated with female properties taken into consideration too. It is likely that the HR15 test configuration is close to the limit for avoiding HR contact for this specific seat setup. Using both datasets (HR15C and HR15NC), each with its corresponding HR contact condition, will be possible in future dummy or model evaluation.